Assessment of the relationships between parents and teachers: Validation and reliability study the parent-teacher relationship scale - Acar, İbrahim Hakkı; Uçuş Güldalı, Şükran (My University, 2017)
This study aims to adapt Parent-Teacher Relationship Scale (PTRS), which was developed by Vickers and Minke (1995) to Turkish and conduct the reliability and validity analyses. The PTRS is a 24-item scale that is designed to assess the quality of the relationships between parents and teachers from their perspectives on two subscales; Joining and Communication. We recruited 150 preschool children’s parents and teachers for the current study from the city of, Kırşehir, Turkey. Children’s age ranged from three to six (M= 4.84, SD= .75). Firstly, the PTRS was adapted to Turkish language and culture. The validity of the scale was measured by Confirmatory Factor Analysis and the difference between the Upper %27 and Lower %27 groups. The internal reliability of the scale was calculated by Cronbach's alpha method. The results of the Confirmatory Factor Analyses showed that the scale has a two-factor structure as in the original version. The CFA model for parent report confirmed that there is a 2-factor model (?2= 351.442 (p < .001), CFI= 0.90, RMSEA= .08 (.07 to .10 at 90% CI), and SRMR = .06. The CFA model for teacher report also confirmed that there is a 2-factor model (?2= 401.805 (p < .001), CFI= 0.90, RMSEA= .08 (.06 to .08 at 90% CI), and SRMR = .08. The analyses showed that the PTRS is a valid, reliable tool for Turkish parents and teachers.

Bu çalışmanın amacı, Vickers ve Minke (1995) tarafından geliştirilen Ebeveyn-Öğretmen İlişkisi Ölçeğini (PTRS) Türkçe'ye adaptasyonu ve geçerlik ve güvenirlik çalışmasıdır. Ebeveyn-Öğretmen İlişkisi Ölçeği (PTRS) ebeveyn öğretmen arasındaki ilişkinin kalitesini öğretmenlerin ve ebeveynlerin bakış açılarıyla değerlendirmek için tasarlanmış, katılma ve iletişim olarak iki alt boyutu olan 24 maddelik bir ölçektir. Mevcut araştırmada katılımcıları Kırşehir il merkezinde okul öncesi eğitime devam eden 150 çocuğun ebeveynleri ve öğretmenleri oluşturmaktadır. Çocukların yaşları 3 yaş ile 6 yaş arasında değişmektedir (M= 4.84, SD= .75). Öncelikle ölçek Türk kültürüne ve diline adapte edilmiş, geçerliği doğrulayıcı faktör analizi ve %27'lik üst grup alt grup farklılığı ile ölçülmüştür. İç güvenirlik Cronbach alpha ile tespit edilmiştir. Doğrulayıcı faktör analizi sonuçları ölçeğin orijinal versiyonunda olduğu gibi iki faktörlü model olduğunu göstermişir. Doğrulayıcı faktör analizi hem ebeveyn (?2= 351.442 (p < .001), CFI= 0.90, RMSEA= .08 (.07 to .10 90% CI), ve SRMR = .06. hem öğretmen ölçeği için (?2= 401.805 (p < .001), CFI= 0.90, RMSEA= .08 (.06 to .08 90% CI), ve SRMR = .08. iki faktörlü bir model ortaya çıkarmıştır. Mevcut çalışmada analizler Ebeveyn-Öğretmen İlişkisi (PTRS) ölçeğinin Türk ebeveynleri ve öğretmenleri için geçerli ve güvenilir bir ölçme aracı olduğunun sonucunu göstermektedir.
Ebeveyn-öğretmen ilişkilerinin değerlendirmesi: Ebeveyn-öğretmen ilişki ölçeğinin geçerlik ve güvenirlik çalışması
Keywords: Parent-Teacher Relationship; Early Childhood; Communication; Confirmatory Factor Analyses; Ebeveyn-Öğretmen İlişkisi; Erken Çocukluk; İletişim; Doğrulayıcı Faktör Analizi